2020
DOI: 10.1007/s11606-020-06253-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Harms of Long-term Opioid Dose Reduction or Discontinuation in Patients with Chronic Pain: a Rapid Review

Abstract: BACKGROUND: Many clinicians are reevaluating the use of long-term opioid therapy (LTOT) for chronic pain in response to the opioid crisis and calls from organizations including the Centers for Disease Control & Prevention to limit prescribing of high-dose opioids. However, this practice change is occurring largely in the absence of data regarding patient outcomes. A 2017 systematic review found inconclusive evidence on the impact of LTOT dose reduction and discontinuation on pain severity and function, quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 55 publications
1
70
0
Order By: Relevance
“…Reviews of interventions designed to support opioid tapering for CNCP generally report that inadequate evidence is available to guide primary care practitioners (PCPs) in their management of opioid reduction for patients experiencing CNCP 4,5,9,12,30,31 . Most of the studies that we identified were conducted in the US, in academic settings, Veteran Affairs clinics, or safety net clinics located in hospitals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviews of interventions designed to support opioid tapering for CNCP generally report that inadequate evidence is available to guide primary care practitioners (PCPs) in their management of opioid reduction for patients experiencing CNCP 4,5,9,12,30,31 . Most of the studies that we identified were conducted in the US, in academic settings, Veteran Affairs clinics, or safety net clinics located in hospitals.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence to suggest that tapering can be achieved without increased levels of pain and loss of functional capacity, especially when tapering occurs slowly 16,19,30 . The biggest gap in evidence lies in evaluating which patients or tapering characteristics are associated with benefit or harm 5 . This gap needs to be addressed to assuage the front‐of‐mind fear for both PCPs and patients, particularly in relation to accidental overdose and adverse events relating to mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 39 Similarly, the Centers for Disease Control and Prevention recommends additional caution for prescribing >50 mg morphine equivalent daily dose (MEDD) and recommends against >90 mg MEDD. 16 In general, the recommendation is to keep opioid therapy at the lowest dosage and shortest duration possible, in conjunction with the implementation of opioid risk mitigation strategies 26 and consideration of issues related to telehealth, care coordination, stepped care model implementation, 19 and suicide prevention. 34 …”
mentioning
confidence: 99%
“…This may include those on low MEDDs who are not appropriate for rescue (ie, “breakthrough”) medications and patients with comorbid complex opioid dependence who may be more appropriate for other OUD treatments (eg, buprenorphine). 26 …”
mentioning
confidence: 99%